Mutations in the PAH gene: A Tool for population genetics study - Stojiljković Maja; Stevanović Ana; Đorđević Maja; Petručev Branka; Tošić Nataša; Karan-Đurašević Teodora; Aveić Sanja; Radmilović Milena; Pavlović Sonja (Archives of Biological Sciences, 2007)
Phenylketonuria (PKU), an inborn error of metabolism, is caused by mutations in the phenylalanine hydroxylase (PAH) gene. In the Serbian population, 19 different PAH mutations have been identified. We used PAH mutations as molecular markers for population genetics study. The low homozygosity value of the PAH gene (0.10) indicates that PKU in Serbia is heterogeneous, reflecting numerous migrations throughout Southeast Europe. The strategy for molecular diagnostics of PKU was designed accordingly. To elucidate the origin of the most common (L48S) PKU mutation in Serbia, we performed haplotype analysis by PCR-RFLP. Our results suggest that the L48S mutation was imported into Serbia from populations with different genetic backgrounds.